A Phase Ib/II Study of Ganetespib With Doxorubicin in Advanced Solid Tumors Including Relapsed-Refractory Small Cell Lung Cancer - Subramaniam, Deepa S.; Liu, Stephen V.; Crawford, Jeanette; Kramer, Jenna; Thompson, Jillian; Wang, Hongkun; Giaccone, Giuseppe (Frontiers in Oncology, 2018)
Introduction Small cell lung cancer (SCLC) accounts for 15% of all lung cancers and is characterized by high response rates to cytotoxic chemotherapy and equally high rates of relapse. Many resistance mechanisms have been proposed including resistance to doxorubicin via induction of a heat shock response. Ganetespib is a novel and potent non-geldanamycin heat shock protein 90 (Hsp90) inhibitor. In preclinical studies, synergy between ganetespib and doxorubicin was shown. We conducted a phase Ib/II study of the safety, tolerability, and preliminary efficacy of the combination of ganetespib and doxorubicin. Methods Patients eligible for the phase Ib portion had advanced tumors that would be appropriate for doxorubicin therapy and those in the phase II portion had relapsed or refractory SCLC. All patients had an ECOG performance status, 0–1 and adequate organ function, including a cardiac ejection fraction ≥50%. Patients who received a lifetime cumulative doxorubicin dose of >150 mg/m2 or who had symptomatic brain metastases were excluded. Patients received ganetespib on Days 1 and 8 and doxorubicin 50 mg/m2 on day 1 in 21-day cycles. Results Eleven patients were enrolled including nine in the phase Ib dose escalation and two in the phase II expansion. The study was terminated by the sponsor. The dose recommended for future study is ganetespib 150 mg/m2 in combination with doxorubicin at a dose of 50 mg/m2. The most common adverse events of the combination were grade 1/2 diarrhea, nausea, fatigue, and transaminitis. No dose limiting toxicities were observed. Response rate was 25% and median duration of response was 137 days. Conclusion Ganetespib plus doxorubicin was a well-tolerated combination and there remains potential for the clinical development of Hsp90 inhibitors in SCLC. Clinical Trial Registration https://ClinicalTrials.gov/ct2/show/NCT02261805, identifier NCT02261805.